Komunikasi Terapeutik Integratif Upaya Relaps Prevention Pada Terapi Pasien ODGJ - Febrian, Risky Wahyu; Wahyuningsih, Sri (Jurnal Keperawatan Muhammadiyah, 2025)
This study aims to look at integrative stakeholder therapeutic communication for relapse prevention efforts in the therapy of PMWD patients at the Kokop Health Center This research was conducted with a qualitative approach using a case study research method. Data were obtained using research instruments in the form of interview guides and observation guides using data collection techniques by conducting in-depth observations and interviews with related parties, namely midwives, doctors, puskesmas officers and mental cadres. The subjects in this study were midwives, doctors and mental cadres as key parties who were directly connected to therapeutic communication with patients The research resulted in the findings of four phases carried out during the integrative therapeutic communication process, namely pre-interaction, introduction, core and termination. The intervention strategies carried out in relapse prevention consist of identification, awareness building, myth elimination and cognitive restructuring. Likewise, the obstacles found during the communication process include distance and terrain, negative outcome expectations, laziness and family self-realization. This study shows that therapeutic communication is the core approach in preventing relapse in PMWD patients at the Kokop Community Health Center to increase patients' self-efficacy so that they are able to manage their mental disorders